Determinants Of Total Loans Disbursed By Rural Banks In Indonesia - Gading, Ratih Laras; Anindyntha, Firdha Aksari (Jurnal Ekonomi, 2024)
The financial sector can influence the process of economic development, one of which is through banking by carrying out its intermediary function. One of the banks that have the function of channelling credit and collecting public funds is the Rural Bank. By using the VECM (Vector Error Correction Model) approach model, this study was conducted to determine the long-term and short-term effects of external factors such as Inflation and BI rate and also on internal factors such as the amount of deposits and non-performing loan rates on the amount of credit in the period 2008 - 2022. The results showed both in the long and short term that the internal factors of deposits and non-performing loans had a significant and negative effect on the amount of credit disbursed. External factors such as Inflation and BI rates do not affect the loan disbursed.